Career Consequences of Firm Heterogeneity for Young Workers: First Job and Firm Size - Jaime Arellano-Bover (Institute of Labor Economics (IZA), 2020)
I study the long-term effects of landing a first job at a large firm versus a small one using Spanish social security data. Size could be a relevant employer attribute for inexperienced workers since large firms are associated with greater training, higher wages, and enhanced productivity. The key empirical challenge is selection into first jobs – for instance, more able people may land jobs at large firms. I address this challenge developing an instrumental-variables approach that, while keeping business-cycle conditions fixed, leverages variation in the composition of labor demand that labor-market entrants face. I find that initially matching with a larger firm substantially improves long-term outcomes such as lifetime income, and that these benefits persist through subsequent jobs. Additional results point to mechanisms related to search frictions and better skill-development at large firms. Together, these findings shed light on how heterogeneous firms persistently impact young workers' trajectories.
Keywords: E24; J23; J24; J31; J62; 330; first job; employer size; firm heterogeneity; young workers; lifetime income; on-the-job skills